Assesment Of the Obligation of Worship, The Ability of Thaharah, and The Ability to Pray in Inpatients at YARSI Hospital - Norwicha Rahmasari Putri; Rifqatussa'adah Rifqatussa'adah; Fathul Jannah (Junior Medical Journal, 2023)
Health in general is a dynamic state of complete physical, mental, spiritual and social well-being (WHO). Spirituality can be interpreted as something that is felt about oneself and relationships with others. Spiritual assessment can include the obligation of worship and the ability to worship. Islamic spiritual guidance is an activity in the form of a process of spiritual guidance and coaching to patients in hospitals in the form of giving motivation, providing guidance on prayer, how to purify (thaharah), pray, and other worship practices. This study aims to determine the assessment of the obligation to worship, the ability of thaharah, and the ability to pray in inpatients at YARSI Hospital. This research method uses a non-experimental quantitative research with a cross-sectional approach. The sampling method of this research was carried out by means of purposive sampling. The population in this study were inpatients at YARSI Hospital for the period May-December 2021, with a sample that met the inclusion criteria of 1703 patients. The instrument in this study was patient spiritual assessment data on the YARSI Hospital information system. The results of the inpatient characteristic study showed that 46.1% of inpatients were in the range of 25-44 years, with 14.5% of patients requiring healing motivation, 22% of patients being able to perform ablution independently, and 17.7% of patients being able to pray while standing. The statistical test results also showed that there was a relationship between the patient's age and the ability to perform thaharah (p=0.000) and the ability to worship (p=0.000). Meanwhile, there is a relationship between gender and thaharah ability (p=0.038). The finding of the relationship between age and gender with the ability to pray and pray indicates the importance of the nurse's role in guiding patients. Therefore, the patient's spiritual assessment is important.